Re-orientate in prison. A training for a new life project - Caterina Benelli; Roberta Paleani (Firenze University Press, 2019)
The article has a twofold focus: on the one hand, it tackles the issue of the end of imprisonment term which represents one of the most critical and problematic phases of detention and, on the other hand, it addresses the matter of how inmates need to be supported in planning their new life project. The question Where are we and where are we going to? is the core of the psycho-pedagogical training course promoted in a correctional facility and experimented with a group of inmates who are close to the end of their imprisonment term and are in need of support and guidance. Accompaniment and support of this transition also respond to a need of the territory to set in motion orientation projects in prison: a place - by its very nature - dis-orienting.   Ri-orientarsi in carcere. Un percorso formativo per un nuovo progetto di vita. Il presente articolo intende mettere in luce la questione del fine pena in carcere che rappresenta una delle fasi più delicate e difficili della detenzione e, allo stesso tempo, di come accompagnare i reclusi alla progettazione del nuovo progetto di vita. La domanda Dove siamo e dove stiamo andando? è il punto di partenza del percorso formativo di tipo psico-pedagogico promosso in un Istituto penitenziario per avviare una sperimentazione con un gruppo di persone in condizione di detenzione, prossimi alla conclusione della pena e con un urgente bisogno di supporto e di orientamento. Accompagnare e sostenere tale attraversamento, rispondono anche ad una necessità del territorio di attivare progetti di orientamento in carcere: luogo - per propria natura - dis-orientante.